2022
DOI: 10.1038/s41591-022-01987-w
|View full text |Cite
|
Sign up to set email alerts
|

Tackling bias in AI health datasets through the STANDING Together initiative

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…These results are surprising given racial categories are imprecise, lack objective definitions, and have varied over time and by geography 25 . Nonetheless, identifying if and when AI may predict race is important for the thoughtful development of equitable applications of AI to medicine 26 . We believe it is equally important to understand how and why AI may predict race.…”
Section: Discussionmentioning
confidence: 99%
“…These results are surprising given racial categories are imprecise, lack objective definitions, and have varied over time and by geography 25 . Nonetheless, identifying if and when AI may predict race is important for the thoughtful development of equitable applications of AI to medicine 26 . We believe it is equally important to understand how and why AI may predict race.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that data from these populations may be used to develop algorithms for patients from outside these regions, it is almost expected that postvalidation real-world model performance would be substandard and that such models incorporate the biases inherent to their training and validation datasets. Initiatives such as the STANDING Together artificial intelligence initiative, which aim to standardize dataset curation, identify and map dataset deficiencies in priority disease areas, and envelop dataset curators into the development process, are an excellent step forward to addressing digital health data sparsity [26]. Within ophthalmology specifically, the American Academy of Ophthalmology's Intelligent Research in Sight Registry also offers clinicians and researchers an accessible repository for ocular data ready for research use, albeit with the caveat of geographic limitation to the United States [27].…”
Section: Approaches To Improve Model Validationmentioning
confidence: 99%
“…[1][2][3][4] While there is consensus that data flow between organizations and developers is necessary to develop AI algorithms, many organizations remain reluctant to share health data for AI due to organizational apprehensions and competing priorities, affecting equitable AI development in the health care sector. [5][6][7][8][9] Current research highlights problematic trends in health data sharing. A systematic review by Kaushal et al 10 highlighted that large data-sharing initiatives are often performed by large academic institutions from a few geographic locations with access to funding and the technical expertise to transform and share well-curated health data sets responsibly.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in algorithm development have shown that artificial intelligence (AI) and machine learning can augment clinical decision-making, promoting diagnostic excellence . While there is consensus that data flow between organizations and developers is necessary to develop AI algorithms, many organizations remain reluctant to share health data for AI due to organizational apprehensions and competing priorities, affecting equitable AI development in the health care sector …”
Section: Introductionmentioning
confidence: 99%